2020
DOI: 10.7762/cnr.2020.9.3.171
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Antioxidant Quality Score and Cardiorespiratory Fitness in Iranian Adults: a Cross-Sectional Study

Abstract: The association between dietary antioxidant quality score (DAQS) and cardiovascular risk factors such as low cardiovascular fitness (CRF) and elevated blood pressure (BP) has rarely been investigated. To investigate the association between DAQS, CRF, and BP. This crosssectional study was conducted on 270 adult subjects living in Tehran, Iran. Dietary intake was evaluated using a validated food frequency questionnaire. The DAQS was calculated using antioxidant-nutrient intake. Socioeconomic status, anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…As far as we know, there is no information about the association between DAQS or specific antioxidant with relative muscle strength. However, there are limited studies that examined the association between DAQS with muscle mass, bone mass or some health problems 15,16 . Most studies have evaluated the association between antioxidant nutrients such as selenium, zinc, and vitamin D, E, and C with muscle mass or oxidative stress which is related to muscle function 38‐41 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as we know, there is no information about the association between DAQS or specific antioxidant with relative muscle strength. However, there are limited studies that examined the association between DAQS with muscle mass, bone mass or some health problems 15,16 . Most studies have evaluated the association between antioxidant nutrients such as selenium, zinc, and vitamin D, E, and C with muscle mass or oxidative stress which is related to muscle function 38‐41 …”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited studies that examined the association between DAQS with muscle mass, bone mass or some health problems. 15,16 Most studies have evaluated the association between antioxidant nutrients such as selenium, zinc, and vitamin D, E, and C with muscle mass or oxidative stress which is related to muscle function. [38][39][40][41] We found that selenium intake is positively associated with HE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations